2021
DOI: 10.1016/j.ijid.2021.03.082
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal trend of renal involvement in COVID-19: A pooled analysis of 17 134 patients

Abstract: Background The spatiotemporal trend of renal involvement in Coronavirus Disease 2019(COVID-19) patients is still unclear. Therefore, we seek to reveal the dynamics of renal involvement superimposed COVID-19 according to time and space. Methods The COVID-19 patients reporting the renal involvement were enrolled in our study. We collected the following information: the first author, patient demographics, patients enrolled period, location, definition of acute kidney injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(125 reference statements)
0
1
0
2
Order By: Relevance
“…(2021) showed that of 17,134 individuals with COVID-19, about 19% had acute kidney injury and 7% required renal replacement therapy [81]. A similar profile was found by Oweis et al ( 2022) in a cohort conducted in Jordan with 1044 patients, of whom 25.3% developed acute kidney injury and 1.8% were referred for renal replacement therapy [82].…”
Section: Renal Systemmentioning
confidence: 55%
“…(2021) showed that of 17,134 individuals with COVID-19, about 19% had acute kidney injury and 7% required renal replacement therapy [81]. A similar profile was found by Oweis et al ( 2022) in a cohort conducted in Jordan with 1044 patients, of whom 25.3% developed acute kidney injury and 1.8% were referred for renal replacement therapy [82].…”
Section: Renal Systemmentioning
confidence: 55%
“…Un análisis temporoespacial del compromiso renal en el contexto de pacientes con COVID-19 consideró 17.134 pacientes de 30 estudios seleccionados (18) . La prevalencia de IRA en los pacientes enrolados antes del 1/3/20 fue significativamente menor que la de los pacientes enrolados en forma posterior (9% versus 36%) (18) . Los pacientes con COVID-19 severa y los no sobrevivientes presentaron un riesgo significativamente mayor de desarrollar IRA y de necesidad de TRR (18) .…”
Section: Discussionunclassified
“…La prevalencia de IRA en los pacientes enrolados antes del 1/3/20 fue significativamente menor que la de los pacientes enrolados en forma posterior (9% versus 36%) (18) . Los pacientes con COVID-19 severa y los no sobrevivientes presentaron un riesgo significativamente mayor de desarrollar IRA y de necesidad de TRR (18) . Muchas series reportadas posteriormente muestran una disminución en el tiempo de la incidencia y severidad de la IRA asociada a COVID-19 que puede estar relacionada a optimización del tratamiento, a un reconocimiento creciente de formas menos severa de IRA, a la virulencia de las diferentes cepas y a la vacunación (13,(19)(20)(21) .…”
Section: Discussionunclassified